Effect of biochar addition on the physicochemical properties of compost from food and garden wastes - Abdullah, Nurul Maisarah (2015)
Food waste contains a high content of biodegradable organic material that can be recycled into compost. The utilization of food and garden wastes for compost production take place efficiently with the action of microorganisms depending on certain parameters such as temperature, aeration, agitation, moisture content, pH value and feedstock composition. Addition of bulking agents such as biochar and sawdust can also improve the carbon content for microbial growth and utilization. The objectives of this study are to investigate the effect of different percentages of biochar on the composting process of food and garden waste and to study the quality of compost produced from food and garden wastes with biochar addition. The In-vessel composting system was applied in this study due to higher flexibility in controlling and monitoring the agitation and aeration system. In physicochemical study, different percentage of biochar (0%, 2%, 4% and 6%) was added to the system separately and the effect on composting process from the addition was evaluated. The quality of compost was assessed by Solvita test and germination test. The addition of biochar has accelerated the onset of thermophilic phase. The system was supplied with sufficient amount of oxygen in range of 7.1 - 21.4%. The moisture content also was maintained below 63.91% for the whole process. After 14 days of composting, finished compost with pH range 6 – 8 was obtained. The Solvita test of compost detected that the compost was not matured yet and not ready to be use. Further composting is needed. The germination rate of the compost within range 10.53% - 42.11% shows that the immature compost contained high level of phytotoxicity. In summary, the composting with 2% biochar has greatly enriched the compost with microbial populations and hence, improved the composting process.